#### Answer

The $\Delta y$ is of 9

#### Work Step by Step

$f(x)=3x+2$
Now increase $x$ by 3,
$\implies$ $f(x+3)=3(x+3)+2=3x+11$
$f(x) - f(x+3) = 9$ =$\Delta y$

Published by
W. H. Freeman

ISBN 10:
1464125260

ISBN 13:
978-1-46412-526-3

The $\Delta y$ is of 9

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.